Effect of static stretching with different rest intervals on muscle stiffness. (11th June 2019) - Nojiri, Shusuke; Ikezoe, Tome; Nakao, Sayaka; Umehara, Jun; Motomura, Yoshiki; Yagi, Masahide; Hirono, Tetsuya; Ichihashi, Noriaki
Abstract: The aim of the study was to investigate the effect of static stretching (SS) with different rest intervals on muscle stiffness. Fifteen healthy males participated in the study. Four bouts of thirty-second SS for the gastrocnemii were performed at the maximal dorsiflexion using dynamometer with two different rest intervals between stretches, namely 0 s (R0) and 30 s (R30). Each participant underwent both stretching protocols at least 48 h apart in a random order. Between each bout of SS, the ankle was moved to 20°-plantar-flexion in 3 s, held for each rest interval time, and then returned to the stretching position in 3 s. The shear elastic modulus of the medial gastrocnemius was measured before (PRE) and immediately after (POST) four bouts of SS to assess muscle stiffness of the medial gastrocnemius. Two-way repeated measures analysis of variance (protocol × time) indicated a significant interaction effect on the shear elastic modulus. The shear elastic modulus significantly decreased after SS in both protocols [R0, PRE: 11.5 ± 3.3 kPa, POST: 10.0 ± 2.6 kPa, amount of change: 1.6 ± 0.9 kPa (13.0 ± 5.2%); R30, PRE: 11.0 ± 2.8 kPa, POST: 10.2 ± 2.1 kPa, amount of change: 0.8 ± 1.3 kPa (6.0 ± 10.4%)]. Furthermore, the SS with 0-s rest interval induced greater decrease in shear elastic modulus when compared to SS with 30-s rest interval (p = 0.023). Thus, when performing SS to decrease muscle stiffness, rest intervals between stretches should be minimized.